The effects of alkaline catalysts in used frying oil biodiesel on the diesel engine performances - Mohd Zamberi, Mahanum; ANI, FARID NASIR; Herawan, Safarudin Gazali (Trans Tech Publications, 2014)
The biodiesel, defined as monoalkyl esters from waste vegetable oils are being produced widely as a viable alternative diesel fuels due to its lower cost, largest producer and reduces the disposal problem. In this study, the effects of catalyst formulation on biodiesel yield are evaluated by using three different alkaline catalyst; sodium hydroxide (NaOH), potassium hydroxide (KOH)and sodium methoxide (NaOCH3) with methanol via transesterification process and are tested in a four cylinder Mitsubishi Pajero 2.5cc Intercooler Turbo Diesel Engine. The engine emissions and performance were recorded under partial load within the range of 1000 to 3500 rpm of the biodiesel (B100) fuels compared with the diesel fuel. The best yield percentage was obtained using NaOCH3 as catalyst whilst KOH is the most convenient and simpler in process. NaOH was found to be more superior than the other two catalysts in terms of lower cost production and low engine emission.